Particle sorting during sediment redistribution processes and the effect on 230Th‐normalized mass accumulation rates. Issue 15 (4th August 2014) - Marcantonio, Franco; Lyle, Mitchell; Ibrahim, Rami
Abstract The 230Th method of determining mass accumulation rates (MARs) assumes that little to no fractionation occurs during sediment redistribution processes at the seafloor. We examine 230Th inventories in radiocarbon‐dated multicore sediments from paired winnowed and focused sites at Cocos and Carnegie Ridges, Panama Basin. Radiocarbon‐derived sand MARs, which likely represent the vertical rain of particles poorly transported by bottom currents, are similar at each of the paired sites but are different using 230Th normalization. 230Th‐normalized MARs are about 60% lower at focused sites and likely underestimate vertical MARs, while the reverse is true for winnowed sites. We hypothesize that size fractionation occurs most frequently at lower current velocities, resulting in the coarse fraction being left behind and primarily the fine 230Th‐rich grains being transported downslope. 230Th‐normalization works well for recording fine‐grained (detrital and opal), but not coarse‐grained (carbonate), fluxes in regions that have undergone sediment redistribution.